Characterization and Evaluation of Antibacterial Activities of Chemically Synthesized Iron Oxide Nanoparticles - Behera, Sudhanshu Shekhar; Patra, Jayanta Kumar; Pramanik, Krishna; Panda, Niladri; Thatoi, Hrudayanath (Scientific Research, 2012)
The iron oxide nanoparticles have been synthesized in co-precipitation method using aqueous solution of ferric and ferrous ions with sodium salt. The synthesis of iron-oxide nanoparticles were validated by UV-Visible spectroscopy which showed higher peak at 370 nm as valid standard reference. An average size of iron oxide nanoparticle found by diffraction light scattering (DLS) particle size analyser, ranges approximately between 10 nm to 120 nm with mean particle size of 66 nm. The X-ray power diffraction (XRD) analysis revealed the crystallographic structure of magnetic particles. Characterization of the mean particle size and morphology of iron oxide nanoparticles confirmed that the iron oxide nanoparticles are nearly spherical and crystalline in shape. Further the antibacterial effect of iron oxide nanoparticles was evaluated against ten pathogenic bacteria which showed that the nanoparticles have moderate antibacterial activity against both Gram positive and Gram negative pathogenic bacterial strains and retains potential application in pharmaceutical and biomedical industries.
Keywords: Iron Oxide; Co-Precipitation; Nanoparticles; Antibacterial Activity